2004
DOI: 10.1037/0278-7393.30.2.343
|View full text |Cite
|
Sign up to set email alerts
|

How Positive Affect Modulates Cognitive Control: Reduced Perseveration at the Cost of Increased Distractibility.

Abstract: A fundamental problem that organisms face in a changing environment is how to regulate dynamically the balance between stable maintenance and flexible switching of goals and cognitive sets. The authors show that positive affect plays an important role in the regulation of this stability-flexibility balance. In a cognitive set-switching paradigm, the induction of mild increases in positive affect, as compared with neutral or negative affect, promoted cognitive flexibility and reduced perseveration, but also inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

47
575
5
10

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 581 publications
(637 citation statements)
references
References 47 publications
47
575
5
10
Order By: Relevance
“…Furthermore, it has been shown that positive mood can facilitate task switching in tasks where novelty in stimulus or response is a major feature (Dreisbach & Goschke, 2004). This was the case in the task measuring cognitive flexibility in the present study (i.e., generating new words).…”
Section: Mood and Cognition In Everyday Life 13supporting
confidence: 47%
“…Furthermore, it has been shown that positive mood can facilitate task switching in tasks where novelty in stimulus or response is a major feature (Dreisbach & Goschke, 2004). This was the case in the task measuring cognitive flexibility in the present study (i.e., generating new words).…”
Section: Mood and Cognition In Everyday Life 13supporting
confidence: 47%
“…Some studies with clinically depressed participants have indeed shown that severe negative affect is associated with more rigid, inflexible thoughts (Grant, Thase, & Sweeney, 2001;Merriam, Thase, Haas, Keshavan, & Sweeney, 1999); but this is not a universal finding (Fossati, Amar, Raoux, Ergis, & Allilaire, 1999). Further evidence from non-clinical populations has also proved to be not entirely consistent (Rader & Hughes, 2005;Dreisbach & Goschke, 2004).…”
Section: Encouragingmentioning
confidence: 99%
“…Persistence and flexibility have been considered two antagonistic metacontrol strategies (i.e., strategies that control cognitive control; Goschke, 2003;Cools & d'Esposito, 2011) that can be considered as the extreme poles of a common metacontrol dimension (Hommel, 2015). Changing tasks and environmental conditions require continuous readjustments of the balance between persistence and flexibility, which induces intraindividual variability (Akbari Chermahini & Hommel, 2010;Dreisbach & Goschke, 2004;Herd et al, 2014;Müller et al, 2007), and people differ systematically with respect to the efficiency of the degree to which this balance can be achieved (Arbula, Capizzi, Lombardo, & Vallesi, 2016;Babcock & Vallesi, 2017; for a review, see Hommel & Colzato, 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…A more pronounced effect of task-irrelevant information would thus indicate a lack of selectivity with respect to the information that the present stimulus ought to (re-)activate, with the result that falsely (re-)activated memory traces compete with task-relevant information for selection. A related, but somewhat different aspect of information-processing efficiency is assessed by an attentional set-shifting task developed by Dreisbach and Goschke (2004). Participants usually perform a letter or digit classification task and the performance is measured before and after the switch to a different version of the task, so that the difference represents set-switching costs.…”
Section: Introductionmentioning
confidence: 99%